Una lectura interpretativa de Tras la virtud, de Alasdair MacIntyre - Fernández-Llebrez, Fernando (Foro Interno, 2010)
This article centers on the thought of Alasdair MacIntyre, whose most prominente work, After Virtue, is considered a classic of political science. In contrast with other reviews, this article will examine After Virtue within the broader context of MacIntyre’s thinking and publications. An overview of MacIntyre’s literary corpus and the evolution of his thinking will shed light on the volume examined and trace certain ideas that are characteristic of this Scottish political philosopher. Matters that remained unsettled in After Virtue have become over time more defined in MacIntyre’s thinking, such as the influence exerted upon him by Thomas Aquinas.